Decentralized fault-tolerant MRAC for a class of large-scale systems with time-varying delays and actuator faults. (March 2019) - Deng, Chao; Yang, Guang-Hong; Er, Meng Joo
Highlights: In contrast with the existing linear large-scale systems literature, a novel cyclic-small-gain condition is introduced to solve the mismatched interconnections of each subsystem. A novel time-invariant controller is developed to solve the model reference adaptive fault-tolerant problem. Different from the traditional method to estimate the weight vector on fuzzy logic systems, only the norm of the weight vector is estimated in this paper. Abstract: This paper considers the decentralized fault-tolerant model reference adaptive control (MRAC) problem for a class of nonlinear large-scale systems with matched unknown nonlinearity and uncertain time delay interconnections and mismatched interconnections. A novel cyclic-small-gain condition is achieved to show the boundedness of tracking errors. Furthermore, by introducing adaptive mechanisms, a new decentralized fault-tolerant controller is developed. In addition, it is shown that the matched unknown nonlinear functions and the matched uncertain time delay functions can be compensated by the developed controller. Compared with existing large-scale systems results, the proposed method is effective to solve the fault-tolerant MRAC problem for large-scale systems with time-varying delays and mismatched interconnections. Finally, the validity is shown by applying the proposed method to a chemical reactor system with two subsystems.